ECOTOURISM DEVELOPMENT OF JAMBI LIBERIKA COFFEE THROUGH STAKEHOLDERS PARTICIPATION APPROACH - Subagyo, Banu; Saipul, Saipul; Ramadlan, Ahmad; Ramdani, M. Yuda; Ramadhona, Yudha; Nonon Saribanon, Nonon Saribanon (Universitas Nasional, 2020)
Liberika coffee is one of leading commodities in Jambi Province and has been registered as a Geographical Indication for West Tanjung Jabung area. In general, Liberika coffee plant is attacked by white fungus, which causes a decrease in production. Its impact on productivity and low prices decreased motivation of farmers to maintain this commodity, and land conversion occurs. In recent years, coffee plants have been converted to areca nut and palm oil which, economically, considered more promising. Even so, Liberika coffee has its own uniqueness, so it needs to be continuously developed. Ecotourism is one of activities that support and maintain the existence of Liberika coffee as a rich biodiversity in Jambi. The key to success and sustainability of this ecotourism development is participation of all stakeholders. For this reason, strengthening farming community as the spearhead of Liberika coffee development, both in personal and institutional capacity.